Can Age at Diagnosis and Sex Improve the Performance of the American Thyroid Association Risk Stratification System for Prediction of Structural Persistent and Recurrent Disease in Patients With Differentiated Thyroid Carcinoma? A Multicenter Study - Zuhur, Sayid Shafi; Aggul, Hunkar; Celik, Mehmet; Avci, Ugur; Erol, Selvinaz; Kilinc, Faruk; Altuntas, Yuksel (Elsevier Inc, 2022)
Objective: Although the age at diagnosis has been suggested as a major determinant of disease-specific survival in the recent TNM staging system, it is not included in the recent American Thyroid Association (ATA) guidelines to estimate the risk of recurrence. Nevertheless, the effect of sex on differentiated thyroid carcinoma (DTC) recurrence is controversial. Therefore, this multicenter study was conducted to assess whether age at diagnosis and sex can improve the performance of the ATA 3-tiered risk stratification system in patients with DTC with at least 5 years of follow-up. Methods: In this study, the computer-recorded data of the patients diagnosed with DTC between January 1985 and January 2016 were analyzed. Only patients with proven structural persistent/recurrent disease were selected for comparisons. Results: This study consisted of 1691 patients (female, 1367) with DTC. In Kaplan-Meier analysis, disease-free survival (DFS) was markedly longer in females only in the ATA low-risk category (P = .045). Nevertheless, a markedly longer DFS was observed in patients aged <45 years in the ATA low- and intermediate-risk categories (P = .004 and P = .009, respectively), whereas in patients aged <55 years, DFS was markedly longer only in the ATA low-risk category (P < .001). In the Cox proportional hazards model, ages of >45 and >55 years at diagnosis and the ATA risk stratification system were all independent predictors of persistent/recurrent disease. Conclusion: Applying the age cutoff of 45 years in the ATA intermediate- and low-risk categories may identify patients at a higher risk of persistence/recurrence and may improve the performance of the ATA risk stratification system, whereas sex may improve the performance of only the ATA low-risk category. (c) 2021 AACE. Published by Elsevier Inc. All rights reserved.
Keywords: ATA risk strati fication system; differentiated thyroid cancer; recurrence; sex; age